Challenges and solutions in Software Defined Networking: A survey - Saraswat S.; Agarwal V.; Gupta H.P.; Mishra R.; Gupta A.; Dutta T. (My University, 2025)
Software Defined Network (SDN) has become one of the most preferred solutions for the management of large-scale complex networks. The network policies in the large-scale network are difficult to embed on entire network devices simultaneously, whereas in SDN these policies can be embedded on the top of the network. The SDN network is divided into two parts which are vertically integrated to form the entire network. The policies and control mechanism are handled by the top layer called the control plane, whereas the data forwarding is performed at the bottom layer called the data plane. Thus the SDN forms a logically centralized network. In this paper, we present a comprehensive survey on the various issues, challenges, and solutions in the designing, implementation, performance, and verification of SDN. The network design emphasized on scalability, fault-tolerance, flexibility, and elasticity. Further implementation issues discuss resource management and virtualization. Similarly, latency, efficiency, and consistency discuss under-performance measure. Lastly, we focus on security and debugging in verification of SDN. We elaborate all the above issues and further discuss the different solutions that exist and discussed the future research trends in SDN. © 2019 Elsevier Ltd